Clinical longevity of direct resin-based composite veneers on anterior teeth (Revista da Faculdade de Odontologia - UPF, 2024)
Introduction: The growing demand for smiles' aesthetic improvement leads direct resin-based composite (RBC) veneers to gain increasing ground when it comes to renewing patients' dental appearance, mainly due to RBC cosmetic properties and the minimally invasive approach related to them. However, it is essential to know the success and survival rates and the main causes of failure of this technique. Objective: The aim of this study was to study the clinical longevity of direct RBC veneers on anterior teeth. Method: PICO framework guided the search strategies in the Pubmed, Google Scholar, and Periódicos Capes databases using a combination of the terms "composite resins, direct veneers, dental veneers, and longevity".Â  Inclusion criteria was clinical follow-up studies of least 6 months, published in English from 2003 onwards, evaluating the performance of RBC veneers in anterior teeth. Books, book chapters, theses, editorials, in vitro studies, and articles that did not provide clinical follow-ups of RBC veneers were excluded. Using language (English) filter, 636 scientific articles were found, which were analyzed following the PRISMA statement and discarded if they did not meet the criteria. At the end, only four articles were selected, and their data collected. Conclusion: There was great variability in the time and criteria used to evaluate restorations in different studies, but the literature considers that direct RBC veneers have an acceptable clinical longevity, but may require repair appointments, and the main cause of failure.